Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/01430750.2014.882863
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an aqueous cerium oxide nanofluid fuel additive on performance and emission characteristics of a compression ignition engine

Abstract: Aqueous cerium oxide at the rate of 50cc per liter was dispersed into diesel and diesel-biodiesel using mechanical agitator and an ultrasonicator for preparing the test fuels. Cerium oxide nanomaterials present in the aqueous cerium oxide exhibit higher catalytic activity because of their large contact surface area per unit volume and can react with water at high temperature to generate hydrogen and improve fuel combustion. Also, cerium oxide nanomaterials act as oxygen buffers causing simultaneous oxidation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 9 publications
0
13
0
1
Order By: Relevance
“…Normally nano additive fuels have a higher calorific value. For instance, the improvement in BTE is achieved by more quantity of fuel to react by way of air due to the higher surface to volume proportion …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally nano additive fuels have a higher calorific value. For instance, the improvement in BTE is achieved by more quantity of fuel to react by way of air due to the higher surface to volume proportion …”
Section: Resultsmentioning
confidence: 99%
“…For instance, the improvement in BTE is achieved by more quantity of fuel to react by way of air due to the higher surface to volume proportion. 16 The BTE was decreased with increasing blends from B10 to B20. This is because of resistance flow of fuel blends are varied it slows down the combustion, atomization, and fuel vaporization.…”
Section: Experimental Set-up and Proceduresmentioning
confidence: 92%
“…Researchers reported enhancements of combustion performance as well as emission characteristics. Possible mechanisms are catalytic processes at the nanoparticle surface as well as increased evaporation rates due to radiation absorption by the particles [83][84][85][86][87][88][89][90][91][92][93][94]. Kao et al as well as Sarkar and Hirani suggested the addition of nanoparticles to brake fluids to improve thermal transport of dissipated braking energy and increase the boiling point to avoid vapor lock [95,96].…”
Section: Automotive Sectormentioning
confidence: 99%
“…Also, it is clear that for all concentration of ZONP there is marked increasing specially at high engine loads. As a response of adding ZONP to the diesel fuel, the BTE improvement could be attributed by the slightly higher peak cylinder pressure and faster heat release rate [24,25].…”
Section: -Brake Thermal Efficiency (Bte)mentioning
confidence: 99%